Research Productivity of Health-care Institutions of Saudi Government: Ten-year Based Bibliometric Analysis - Walid A Zaher; Sultan A Meo; Majid Abdulrahman Almadi; Khalid Fouda Neel (Wolters Kluwer Medknow Publications, 2018)
Background: Saudi Arabia has recognized the significance of scientific research in social, health-care, and economic transformation and has established a large number of advanced research institutes. This study aimed to investigate the research progress of various universities and research institutes of Saudi Arabia during 2006-2016. Methods: In this bibliometric analysis, we investigated research publications published by a number of well-recognized health-care institutions and research centers to authenticate the scientific research productivity in Saudi Arabia during 2006-2016. The Saudi public institutions were selected based on their research activity in the field of medical and health science. The research publications were recorded from Institute of Scientific Information-Web of Science, Thomson Reuters (Clarivate Analytics). Results: During 2006-2016, King Saud University (KSU) published the highest number of publications (9954) followed by King Faisal Specialist Hospital and Research Center (KFSHRC) (3886). Moreover, King Abdulaziz Medical City published 685 articles, King Fahad Medical City 486, King Khaled Eye Specialist Hospital 425, Riyadh Military Hospital 165, and Prince Sultan Cardiac Centre and Research Centre published 108 articles. KSU's contribution to medical and health sciences was 63.4% followed by KFSHRC at 24.7% and the rest of the institutions contributed 12% of research publications. Conclusions: In Saudi Arabia, KSU produced the highest number of research articles during 2006-2015. This high research productivity shows the leadership visionary approach, proper spending of the research funding, and their faculty members' contributions.